Educational governance for the regulation of industry sponsored continuing medical education in interventional and device based therapies. Issue 6 (13th May 2005) - Morgan, J M; Marco, J; Stockx, L; Zannad, F
Abstract : The relationship between industry and clinicians in educational programmes needs to be regulated. Industry may be best placed to deliver educational programmes in "craft" related specialties and particularly in areas where device implantation/technology based therapy has a major clinical role. The authors supervise industry sponsored clinical teaching at a purpose built independent teaching facility, and have developed the concept of educational governance to regulate their relationship with their industry sponsor and that concept is presented.